Evaluation of sustainable feeds for “caviar” production in the Mediterranean sea urchin Paracentrotus lividus (Lamarck, 1816) - Ciriminna L.; Rakaj A.; Grosso L.; Pensa D.; Fianchini A.; Mazzola A.; Vizzini S. (Aquaculture Reports, 2024)
To improve the sustainability of aquaculture practices, a step towards the use of alternative nutrient sources (such as food processing discards) may secure the future of aquaculture sector, namely for emergent species, such as sea urchins. In this context, adult females of the commercial sea urchin Paracentrotus lividus were reared using four feeds based on lettuce discards (72%) and enriched (8%) with an animal-source ingredient (fish Sardina pilchardus, Feed-S; krill Euphausia superba, Feed-K; mussel Mytilus galloprovincialis, Feed-M; anchovy Engraulis encrasicolus discards, Feed-AD). A fifth feed, used as control treatment, was composed of macroalgae (Laminaria sp. and Ulva sp., Feed-UL). Feed performance was evaluated employing a new productive protocol, the Raking method, which propose testing feed effects on sea urchin caviar (oocytes rather than gonads) production. Thus, ingestion rates and absorption efficiency were measured to evaluate feed palatability. Somatic growth and caviar production, expressed introducing the ovosomatic index (OI) instead of the traditional gonadosomantic index, were measured to assess feed productive performances. Caviar quality was assessed by nutritional content and color. Ingestion rate results showed that all feeds were palatable, while findings on absorption efficiency showed differences between the five proposed feeds, with Feed-M and Feed-AD presenting the worst results. Somatic growth was promoted regardless the provided feeds, while OI resulted higher with Feed-K and Feed-M than the other feeds. All produced caviar resulted suitable for human consumption with high protein and fatty acid content, but caviar produced by Feed-UL showed the poorest nutritional profile. Similarly, Feed-UL led to the production of caviar with the lowest quality color, while Feed-S showed the best orange color. Lettuce-based feeds were therefore effective for feeding P. lividus as they stimulated production of high quality caviar. Findings support the exploitation of food discards for the ...